2014
DOI: 10.1007/s00248-014-0537-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bacterial and Archaeal Community Structure in Swine Wastewater Treatment Processes

Abstract: Microbial communities from two field-scale swine wastewater treatment plants (WWTPs) were assessed by pyrosequencing analyses of bacterial and archaeal 16S ribosomal DNA (rDNA) fragments. Effluent samples from secondary (anaerobic covered lagoons and upflow anaerobic sludge blanket [UASB]) and tertiary treatment systems (open-pond natural attenuation lagoon and air-sparged nitrification-denitrification tank followed by alkaline phosphorus precipitation process) were analyzed. A total of 56,807 and 48,859 high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 69 publications
2
21
0
3
Order By: Relevance
“…Firmicutes was reported to be predominant in biogas fermenter (Jaenicke et al 2011), fermentation liquor from rice straw (Zhao et al 2012), autotrophic denitrification biocathode (Xiao et al 2015), and swine WWTPs (Da Silva et al 2015). Lee et al enriched class Clostridia in phylum Firmicutes for bioelectrochemical denitrification.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Firmicutes was reported to be predominant in biogas fermenter (Jaenicke et al 2011), fermentation liquor from rice straw (Zhao et al 2012), autotrophic denitrification biocathode (Xiao et al 2015), and swine WWTPs (Da Silva et al 2015). Lee et al enriched class Clostridia in phylum Firmicutes for bioelectrochemical denitrification.…”
Section: Discussionmentioning
confidence: 98%
“…It is known that Clostridia inhabit diverse anaerobic environments including soil, sediments, fresh water, and anaerobic digesters (Karanasios et al 2010), and some of them (e.g., Clostridium perfringens, Clostridium butyricum, Clostridium denitrificans, Clostridium aminobutyricum, and Clostridium tertium) are capable of denitrification (Hasan and Hall 1977;Lee et al 2013). Da et al investigated bacterial archaeal community and demonstrated that Firmicutes was predominant in swine wastewater treatment processes (Da Silva et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 122,321 sequences, around 98.8% sequences were classified up to phylum Euryarchaeota. Euryarchaeota are known to inhabit pig feces and mostly dominated by the methanogenic members of this phylum (Cardinali-Rezende et al 2012; Da Silva et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…During storage the swine manure slurry decomposes, and emits a considerable quantity of methane (EPA 2013), which is exclusively generated by methanogenic archaea (Whitman et al 2006). Over the past decade, several studies have characterized the archaeal community present in swine feces and stored manure slurry by using both cultivation-based (Miller et al 1986) and culture-independent methods (Whitehead and Cotta 1999; Mao et al 2011; Da Silva et al 2014). However, it is still not clear what underlying ecological processes are important in structuring the community composition of archaea in swine manure slurry.…”
Section: Introductionmentioning
confidence: 99%
“…However, most if not all of these approaches are not economically feasible. Therefore, biological anaerobic digestion followed by stabilization ponds are the most common treatment option adopted in swine farming worldwide [3,6,7]. Pathogen elimination can occur under thermophilic conditions, but not under mesophilic conditions that prevail in most digesters [8].…”
Section: Introductionmentioning
confidence: 99%